Measurement Repeatability of Central and Peripheral Blood Pressures: The ARIC Study - Yong, Fran (Am J Hypertens, 2017)
BACKGROUND: Central systolic and pulse pressures are markers of risk for small vessel disease in the brain and kidneys. The extent to which these markers are reproducible in the setting of population studies is less well established. We estimated short-term repeatability of central systolic and pulse pressures, and those of their peripheral measures for comparison. METHODS: Participants aged 65 years and over (n = 79, 56% women) were drawn from the 2011–2013 examination of the ARIC cohort. Measurements were obtained with automated devices in the supine position, except for conventional sitting pressures, from paired measurements at each of 2 visits separated by 4 to 8 weeks. Three-level variance component models with between-participant, between-visit, and within-visit components estimated reliability metrics. RESULTS: Mean central systolic and pulse pressures were higher than conventional brachial measures, yet their 4 to 8 week measurement repeatability was similar: reliability coefficients were 0.62 (95% confidence interval: 0.49, 0.74) and 0.63 (0.51, 0.76) for central and sitting brachial systolic pressures, and 0.66 (0.54. 0.77) and 0.73 (0.63, 0.82) for their corresponding pulse pressures. Between-participant variation contributed to two-thirds of the short-term repeatability for all measures. Within-visit variation remained uniformly low across visits. CONCLUSIONS: Our results indicate that the average of 2 standardized measurements obtained at a single visit can provide reliable estimates of central systolic and pulse pressures. The reliability coefficients of central and peripheral blood pressure measures were comparable. Estimates are presented of minimal detectable change and difference to aid in study design and evaluation of analytic results.